Great Britain Smart Meter Roll-out Programme: Customer Engagement Strategy for E.ON - lu, chang ling; shetty, harshitha; lu, man man (2010)
In order to reduce carbon emission and manage energy demand, UK government has made smart meter roll-out a mandate. Energy suppliers have been given the instruction to have smart meter installed in all household in GB by 2020. The objective of this report is to formulate a customer engagement strategy for E.ON UK, an energy supply company, to increase its customer engagement level during the roll-out and to conduct the roll-out in a cost-effective manner, while at the same time reinforce customer loyalty and gain their trust. Information has been collected through face-to-face survey and individual interviews with Nottingham local residential. Findings analysed from the dimension of demographic factor in this study has shown that:  People in different age groups have different awareness level, preferred communication channel, contents that they are interested in and preferred way to book appointment.  For the requirement during the installation, people share similar opinion in terms of security concern, trust and preferred way to be educated; An early deployment for proactive customers is recommended for E.ON to carry on before the mass roll-out as a learning experience. According to our study, a four-phase customer engagement and communication strategy is established which includes:  Pre-installation communication: based on the understanding of customers’ awareness about smart meter and its benefits which will motivate customers to 4 have it installed, to deliver the appropriate information to different people through preferred communication channels and trusted source;  Appointment booking: based on the understanding of customer preferred booking channel, installation timing and required pre-installation information to ensure customers can book the appointment easily  During installation based on the understanding of customers’ concern, requirement to grant access and the preferred way to be educated about smart meter usage, create good customer experience during installation.  Post Installation: provide recommendation about post-installation customer communication and support. A successful engagement strategy should be continuously assessed and improved with full commitment from E.ON’s management to create a sustainable competitive advantage for the company.